The Effectiveness of Shockwave Therapy and Stretching Exercises in Chronic Neck Pain - Abdalhaleim Shibani; Sedik Abokdeer (AlQalam Journal of Medical and Applied Sciences, 2025)
This study investigates the effectiveness of stretching exercises combined with radial shockwave therapy in alleviating myofascial trigger points (MTrPs) in a patient diagnosed with mechanical neck pain. The primary objectives were to relieve MTrPs, strengthen cervical musculature, improve range of motion, and enhance functional neck performance. To achieve these goals, the researchers employed an experimental single-subject design, utilizing pre- and post-intervention measurements to evaluate treatment outcomes. The study sample consisted of a 38-year-old male patient presenting with four MTrPs in the upper trapezius muscle. The intervention was conducted at Alhilal Center in Gharyan, Libya, comprising 12 physiotherapy sessions administered over four weeks on alternate days. Assessment tools included the Numerical Pain Rating Scale (NPRS) for pain intensity, a goniometer for cervical range of motion, manual muscle testing grades for muscle strength, and the Functional Pain Scale to evaluate improvements in daily activities. Percentage improvement was used to analyze the results. The findings revealed a 60% reduction in pain levels, a 26.74% improvement in range of motion, a 22.5% increase in muscle strength, and a 66% enhancement in functional pain scores. These results demonstrate that the combined treatment protocol effectively alleviates myofascial trigger points and improves clinical outcomes in patients with mechanical neck pain.